Leadership Styles, Organizational Climate and Work Engagement of Teachers in Region XII: An Explanatory Sequential Design - B. Tejero, Erhardie Priel; Aoanan, Grace (The Future of Education Journal, 2024)
Work engagement reflects teachers' dedication, motivation, and active involvement in their roles. It has emerged as one of the greatest challenges in today’s workplace with serious and potentially lasting repercussions for the global economy (Mann & Harter, 2016). This study aimed to know the status and determine the influence of leadership styles, organizational climate and work engagement of teachers in Region XII. The participants were the teachers from the public secondary schools in Region XII, Philippines who served as respondents for the quantitative phase and were purposely selected for the qualitative phase. The researcher made use of validated adapted survey questionnaires and in-depth interview guide to collect relevant data. Regression and thematic analysis were used to analyze the corresponding data gathered. In the quantitative phase, the findings revealed that the status of leadership styles is moderate; organizational climate is very high; and work engagement is very high. It revealed further that leadership styles were found to be not significant predictor of work engagement while the organizational climate was found to be significant predictor of work engagement. It also showed that the two predictors combined had a significant influence on work engagement. In the qualitative phase, the leadership styles are confirmed a very moderate level for leadership styles while confirmed very high rating in two variables emerged. Finally, findings of the data integration showed that leadership style does not affect senior high school teachers’ work engagement, but the organizational climate is a key factor in predicting their engagement. Hence, the nature of integration is connecting-discordance.